Mathematical Modeling the Electrical Impedance of Piezoceramic Disk Oscillating in Wide Frequency Range (Part 2. Medium Frequencies) - C. V. Bazilo; E. V. Faure; L. M. Usyk; V. V. Tuz; A. M. Chornii (Vìsnik Nacìonalʹnogo Tehnìčnogo Unìversitetu Ukraïni Kììvsʹkij Polìtehnìčnij Ìnstitut: Serìâ Radìotehnìka, Radìoaparatobuduvannâ)
This paper presents further developments in mathematical modeling of the electrical impedance of a piezoceramic disk in a wide frequency range, specifically focusing on the mid-frequency range, i.e., when the elastic wavelength becomes commensurate with the radius of the piezoceramic disk, which is important for numerous modern applications. A mathematical model was developed for disk piezoelectric transducers made of piezoceramics to estimate their electrical impedance and quasi-static electrical capacity in the medium frequency range basing on their geometrical, physical, and mechanical characteristics. The research has found that a piezoceramic disc attains electromechanical anti-resonance in the medium frequency range at frequency, at which its electrical impedance follows to infinity. This effect is due to the polarization charges being completely compensated by the electric charge, when the electric current vanishes and energy consumption from the generator is absent. The calculations proved that at frequencies close to the first thickness resonance (corresponding to the dimensionless wave number from 40 to 60), the radial displacements of material particles of the disk vanish. A very rapid decrease in the levels of radial shifts with a simultaneous increase in the electromechanical resonance number was noted. The evaluation of the mechanical quality factor of piezoceramic disk elements, obtained with the developed mathematical model, closely correlates with real values, which is confirmed by the high agreement between theoretical and experimental results.